Esophageal Gastrointestinal Stromal Tumor with Rare Intracranial Metastasis. (12th October 2020) - Carvalho, José; Teixeira, Margarida; Silva, Francisco Teixeira; Esteves, Alexandra; Ribeiro, Carlos; Guerra, Diana
Abstract : Introduction . Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors and constitute the largest group of nonepithelial digestive neoplasms. However, they do not represent more than 1% of primary digestive tumors. They commonly metastasize to the liver and peritoneum, but brain metastases are extremely rare. Clinical Case . A 76-year-old woman with a diagnosis of esophageal GIST with liver and lung metastases for 13 years, medicated with imatinib, is presented. She was brought to the emergency department after falling and due to changes in behavior and vertigo with 24 hours of evolution. On physical examination, she presented changes in behavior, dysarthria, dysmetria on the right, gait imbalance, and no motor or sensory deficits. On brain computed tomography and posteriorly on magnetic resonance, 2 lesions were observed, left frontal and right cerebellar, compatible with metastatic lesions. After contribution of neurosurgery, histology was obtained that confirmed the lesions were GIST metastases. Imatinib was maintained, and whole brain radiotherapy was performed. After 6 months, she died. Discussion . The rarity of GIST brain metastases is noteworthy, and because of that, there is not enough experience to be certain of the best treatment. Our patient lived for 13 years with excellent disease control with imatinib, but the fact that it does not cross the blood-brain barrier makes it not useful in preventing or treating brain lesions. New tyrosine kinase inhibitors that may cross the blood-brain barrier could be the answer to these cases.